Ecto-5'-nucleotidase: a candidate virulence factor in Streptococcus sanguinis experimental endocarditis. - Jingyuan Fan; Yongshu Zhang; Olivia N Chuang-Smith; Kristi L Frank; Brian D Guenther; Marissa Kern; Patrick M Schlievert; Mark C Herzberg (PLoS ONE, 2012)
Streptococcus sanguinis is the most common cause of infective endocarditis (IE). Since the molecular basis of virulence of this oral commensal bacterium remains unclear, we searched the genome of S. sanguinis for previously unidentified virulence factors. We identified a cell surface ecto-5'-nucleotidase (Nt5e), as a candidate virulence factor. By colorimetric phosphate assay, we showed that S. sanguinis Nt5e can hydrolyze extracellular adenosine triphosphate to generate adenosine. Moreover, a nt5e deletion mutant showed significantly shorter lag time (P<0.05) to onset of platelet aggregation than the wild-type strain, without affecting platelet-bacterial adhesion in vitro (P=0.98). In the absence of nt5e, S. sanguinis caused IE (4 d) in a rabbit model with significantly decreased mass of vegetations (P<0.01) and recovered bacterial loads (log(10)CFU, P=0.01), suggesting that Nt5e contributes to the virulence of S. sanguinis in vivo. As a virulence factor, Nt5e may function by (i) hydrolyzing ATP, a pro-inflammatory molecule, and generating adenosine, an immunosuppressive molecule to inhibit phagocytic monocytes/macrophages associated with valvular vegetations. (ii) Nt5e-mediated inhibition of platelet aggregation could also delay presentation of platelet microbicidal proteins to infecting bacteria on heart valves. Both plausible Nt5e-dependent mechanisms would promote survival of infecting S. sanguinis. In conclusion, we now show for the first time that streptococcal Nt5e modulates S. sanguinis-induced platelet aggregation and may contribute to the virulence of streptococci in experimental IE.